A convection‐permitting numerical study of diurnal cycles of pre‐summer rainfall over southern China. (26th October 2022) - Lu, Xi; Wang, Yao; Qiu, Yueping
Abstract: In this study, the convection‐permitting model (CPM) with 3‐km horizontal resolution has been used to investigate the simulated ability on diurnal cycles of pre‐summer rainfall over southern China with various subregions and rainfall systems. Compared with the observations, the model captures the peak time of nocturnal rainfall in the western inland related to the eastward‐propagating rainfall system over the eastern slope of the Yungui Plateau. The simulated eastward‐propagating rainfall system moves a short distance and has a short lifetime due to the weaker westerly‐steering flow and southerly winds in the late night bringing less warm and moist air with the weaker upward flow of the mountain–plain solenoid circulation that is unfavorable for convection instability. Over the eastern inland, the model shows good performance on simulating the quasi‐stationary rainfall system in the morning because of the high resolution of topography. However, the model cannot simulate the climatology of the secondary morning rainfall peak due to overestimation of the rainfall from noon to evening. On the other hand, the weaker simulated southwesterly winds especially on the north side of the Nanling Mountains with decreased upward movement and moisture convergence and the more stable atmospheric condition lead to the disadvantage of convective rainfall. The CPM reproduces the afternoon rainfall peak but with a lead of 2–3 hr and still cannot simulate the morning peak well over the coastal region. The main source of mode bias is the overestimation of the onshore winds in the boundary layer over the land with the reduced temperature difference between land and sea resulting in insufficient convergence in the coastal region. Abstract : Schematic plot showing three nocturnal and morning rainfall systems over various regions in Southern China. The convection‐permitting model can reproduce the spatial distribution of the pre‐summer rainfall over southern China but overestimates the afternoon precipitation and underestimates the morning rainfall. The model has been evaluated on its reproduction of the nocturnal eastward‐propagating rainfall system in the western inland, the quasi‐stationary morning rainfall system over the eastern inland and the coastal rainfall system in the coastal region. Possible reasons for the model's bias of the nocturnal and morning rainfall related with the acceleration of southwesterly winds in the late night have been investigated.